Delivering the financing needed to progressively realize the right to education - Archer, David (Frontiers in Education, 2026)
There is an obligation on states and the international community to mobilize the maximum of available resources for the progressive realization of the right to education. But in most parts of the world, public education systems have been chronically underfunded for decades, in particular owing to the IMF’s coercive policy advice on austerity. This has exacerbated inequalities and created space for different forms of privatization - as a growing number of people opt out of failing public provision. But there are alternatives, not least those laid out at the Heads of State Transforming Education Summit in 2022. The focus needs to be on enhancing sustainable domestic financing for education. Aid and loans only make up 3% of funding for education with domestic resource mobilization making up 97%. Whilst some progress can be made by encouraging government to spend 20% of their national budgets on education, true transformation depends on national and international action on the size of overall government budgets – engaging strategically on tax justice, debt justice and ending austerity.